PENGARUH GOOD GOVERNANCE, SISTEM PENGENDALIAN INTERN PEMERINTAH DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEMERINTAH DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Rokan Hilir) - Chici Claraini; Enni Savitri; Meilda wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of good governance, internal control system the government and style leadership on the performance of local government in District Government in Rokan Hilir. The research samples are selected by using questionnaire survey method were many as 124 people are respondents. The population in this study is 31 working units Rokan Hilir district. The analytical tool used is multiple regression assisted with SPSS Windows ver 19. The results showed of good govermance, internal control system the government and style leadership significant effect on the performance government. In this research the size of the influence inflicted R square of 0,663 shows that variable good governance, internal control system the government and the style leadership simultaneously explain performance variables of 13,8% while the rest 86,2% influenced by other variable not guilty in this study. .Keyword : Good Governance, Internal Control System the Government, Style Leadership and The Performance Government